Primary Non-Hodgkins Orbital lymphoma of diffuse large B-cell type: a rare presentation (Bangladesh Journal of Medical Science, 2016)
Primary Non-Hodgkins lymphoma of the orbit is a rare presentation and the diffuse large B-cell lymphoma (DLCL) type of histology is much less commoner than the mucosa associated lymphoid tissue (MALT) and follicular lymphoma. A 70 years female patient presented with palpable mass arising from right orbit and proptosis of the right eye. CT scan suggested homogenous enhancing soft tissue mass affecting right lacrimal region without any bony destruction. Biopsy confirmed it to be a case of Primary non-Hodgkins lymphoma of diffuse large B-cell type with strongly positive CD 20. She was given 6 cycles of chemotherapy with R-CHOP after surgery. The patient is now asymptomatic one year after the last cycle of the chemotherapy.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.624-627